2022
DOI: 10.1002/clt2.12153
|View full text |Cite
|
Sign up to set email alerts
|

Leptin favors Th17/Treg cell subsets imbalance associated with allergic asthma severity

Abstract: Background Obesity has often been associated with severe allergic asthma (AA). Here, we analyzed the frequency of different circulating CD4+T‐cell subsets from lean, overweight and obese AA patients. Methods Mononuclear cells from peripheral blood were obtained from 60 AA patients and the frequency of different CD4+T‐cell subsets and type 1 regulatory B cells (Br1) was determined by cytometry. The effect of obese‐related leptin dose on cytokine production and Treg cell function in AA‐derived CD4+ T cell cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…De Rosa and colleagues demonstrated that neutralizing leptin monoclonal antibodies enhances the proliferation of Tregs [ 160 ]. Furthermore, leptin decreases IL-10 production from CD4+ T cells from patients with asthma [ 161 ]. In line with previous findings, Wang et al showed that leptin receptor antagonist promotes Foxp3 and inhibits IL-17 in the thyroid gland of a mouse model with experimental autoimmune thyroiditis [ 162 ].…”
Section: Leptinmentioning
confidence: 99%
“…De Rosa and colleagues demonstrated that neutralizing leptin monoclonal antibodies enhances the proliferation of Tregs [ 160 ]. Furthermore, leptin decreases IL-10 production from CD4+ T cells from patients with asthma [ 161 ]. In line with previous findings, Wang et al showed that leptin receptor antagonist promotes Foxp3 and inhibits IL-17 in the thyroid gland of a mouse model with experimental autoimmune thyroiditis [ 162 ].…”
Section: Leptinmentioning
confidence: 99%
“…Leptin also activates pro-inflammatory Th17 cells [ 124 ]. Leptin elevated Th17 cytokine levels while reducing the function of Treg cells in the culture of CD4 + T cells from lean allergic-asthma patients [ 121 , 125 ]. Leptin shifts T-helper (Th) cells to Th1 cells by producing IFN-γ [ 126 ].…”
Section: Leptin and Asthmamentioning
confidence: 99%
“…Adipose tissue has endocrine functions and promotes a cascade of pro-inflammatory cytokines and adipokines, including leptin, which may be a key factor in the pathology of asthma [27,37,38]; this is because the adipokine may induce changes in the mechanics and functions of the lungs via bronchial inflammation on admission, compared to the stable phase of the disease [42][43][44], mainly due to the accumulation of leptin-producing monocytes in the airway [45]. These ultimately favor the expansion in Th17 cells and the decrease in regulatory T cells [46]. In addition, leptin has been suggested to promote airway inflammation via upregulation of the mitochondrial reactive oxygen species/NOD-, LRR-, and the pyrin domain-containing protein 3 (mostly known as mtROS/NLRP3) inflammasome signaling pathway in human normal BEAS-2 bronchial epithelial cells in vitro [47].…”
Section: Discussionmentioning
confidence: 99%